2022
DOI: 10.1186/s12987-022-00391-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel localization of folate transport systems in the murine central nervous system

Abstract: Background Folates are a family of B9 vitamins that serve as one-carbon donors critical to biosynthetic processes required for the development and function of the central nervous system (CNS) in mammals. Folate transport is mediated by three highly specific systems: (1) folate receptor alpha (FRα; FOLR1/Folr1), (2) the reduced folate-carrier (RFC; SLC19A1/Slc19a1) and (3) the proton-coupled folate transporter (PCFT; SLC46A1/Slc46a1). Folate transport into and out of the CNS occurs at the blood–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…A previous in vitro study examined the transport kinetics of folate in rat inner BRB model and identified RFC1 as the primary responsible transporter for folate by examining RFC1 at the mRNA level [ 45 ]. Besides, a recent study characterized the localization of folate transporters, hence RFC1 expression at CNS barriers in detail focusing especially on BBB cells including the endothelial cells; however, this study explored neither the retina nor pericytes [ 46 ]. So, our study offers a recognition for the roles of RFC1 protein in the CNS and deepens our understanding of other critical functions as well as novel treatment strategies for brain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study examined the transport kinetics of folate in rat inner BRB model and identified RFC1 as the primary responsible transporter for folate by examining RFC1 at the mRNA level [ 45 ]. Besides, a recent study characterized the localization of folate transporters, hence RFC1 expression at CNS barriers in detail focusing especially on BBB cells including the endothelial cells; however, this study explored neither the retina nor pericytes [ 46 ]. So, our study offers a recognition for the roles of RFC1 protein in the CNS and deepens our understanding of other critical functions as well as novel treatment strategies for brain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…RFC1 expression at the protein level in endothelial cells and pericytes of retina has never been studied before, despite its consistent detection in transcripts of microvascular mural cells (pericytes and vascular smooth muscle cells) of the brain (39). Recently, a study characterized the localization of folate transporters, hence RFC1 expression at CNS barriers in detail focusing especially on BBB cells including the endothelial cells; however, this study explored neither the retina nor pericytes (40). So, our study bears another focus, and offers a recognition for the roles of RFC1 in the CNS and deepens our understanding of other critical functions as well as novel treatment strategies for brain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Some organic anionic and cationic drug transporters were only expressed in the former. Sangha et al [ 84 ] have found two important folate transporters, the reduced folate-carrier and the proton-coupled folate transporter, are present at the blood-arachnoid barrier.…”
Section: Elements Of the Blood-csf Barrier And The Csf And Glymphatic...mentioning
confidence: 99%